2001
DOI: 10.1111/1469-8986.3840685
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of frontal EEG asymmetry through biofeedback alters self‐reported emotional responses and facial EMG

Abstract: Individual differences in resting asymmetrical frontal brain activity have been found to predict subsequent emotional responses. The question of whether frontal brain asymmetry can cause emotional responses has yet to be addressed. Biofeedback training designed to alter the asymmetry of frontal brain activity was therefore examined. Eighteen right-handed female participants were randomly assigned to receive biofeedback training designed to increase right frontal alpha relative to left frontal alpha~n ϭ 9! or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 40 publications
6
84
1
Order By: Relevance
“…They suggest that avatars could eventually serve alternative clinical approaches such as virtual reality immersion and HCI Birbaumer et al, 2009; Renaud et al, 2010). It could be hypothesized, for instance, that better detection of other’s facial expressions would be achieved through biofeedback based on facial EMG and avatars reacting with corresponding expressions (Allen et al, 2001; Bornemann et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…They suggest that avatars could eventually serve alternative clinical approaches such as virtual reality immersion and HCI Birbaumer et al, 2009; Renaud et al, 2010). It could be hypothesized, for instance, that better detection of other’s facial expressions would be achieved through biofeedback based on facial EMG and avatars reacting with corresponding expressions (Allen et al, 2001; Bornemann et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported shifts in frontal hemispheric EEG dominance during meditation, hypnosis, and imagery, although the specific regional patterns of EEG activation depend upon the particular components of the therapeutic intervention (49, 130134). Relative decreases in right-sided PFC activation were also found among patients with major depression following treatment with interpersonal psychotherapy (135), sessions of psychotherapy (136), and with neurofeedback (brainwave biofeedback) (137). Finally, studies by Jones and colleagues (138, 139) have demonstrated functional alterations in frontal EEG hemispheric asymmetry following massage therapy.…”
Section: Experimental Approaches To Assess Mechanisms and Efficacy Ofmentioning
confidence: 99%
“…Although resting frontal brain asymmetry shows high internal consistency (Towers and Allen, 2009) and reasonable stability over time (Hagemann et al, 2002; Allen et al, 2004b), there exists considerable variability within the resting assessment period, with non-depressed individuals demonstrating relatively greater left frontal activity approximately 70% of the time, and relatively greater right activity the remainder (Baehr et al, 1998; Allen et al, 2001). Such findings suggest that there may indeed be meaningful variability within the resting assessment period that deserves greater scrutiny, and that the assumption that resting EEG asymmetry is a trait may need to be reframed to reflect a recurring series of states within the resting period.…”
Section: Introductionmentioning
confidence: 99%